Perkembangan Pemahaman Radikalisme di Indonesia - Imran Tahir; Irwan Tahir (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
Radicalism is a threat to the security and peace of a community, even a threat to the survival of a nation. Experience in a number of countries shows that radicalism can encourage conflict, both horizontally and vertically. Radicalism can be interpreted as positive or negative or constructive and descriptive. Radicalism is positive or constructive if it is lined with tolerance or restraint in society. In Indonesia, the danger of negative radicalism is evident when many young people are exposed to ideas that lead to violence.